Application and prospects of block caving mining technology in China - Yuming, L.; Changnian, X.; Xiaowei, C.; Wen, L.; Qingang, C.; Haohao, W.; Shenqing, X. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Block caving mining is a large-scale, low-cost underground mining technology that has been in use for over a hundred years. Since China began adopting block caving mining technology in the 1980s, three block caving mines have been built and are in operation (Tongkuangyu mine, Pulang copper mine, and the western section of Yanqianshan iron ore mine), three mines are under construction (Panjiatian iron ore mine, Haoyao’erhudong gold mine and Yandong copper mine), and several others are in the preliminary research and approval stages. China now has a relatively high number of block caving mining applications. This paper systematically introduces the basic information of block caving mines in operation, under construction, or planned in China, as well as related technological research achievements in block caving mining. In the context of China's mining industry development, it analyses the challenges and opportunities for promoting the application of block caving mining technology in low-grade, thick deposits of copper, iron and other minerals in China, along with the urgent research directions that require further in-depth study.